Using mercury stable isotope fractionation to identify the contribution of historical mercury mining sources present in downstream water, sediment and fish - Eckley, Chris S.; Eagles-Smith, Collin; Luxton, Todd P.; Hoffman, Joel; Janssen, Sarah (Frontiers in Environmental Chemistry, 2023)
Ecosystems downstream of mercury (Hg) contaminated sites can be impacted by both localized releases as well as Hg deposited to the watershed from atmospheric transport. Identifying the source of Hg in water, sediment, and fish downstream of contaminated sites is important for determining the effectiveness of source-control remediation actions. This study uses measurements of Hg stable isotopes in soil, sediment, water, and fish to differentiate between Hg from an abandoned Hg mine from non-mine-related sources. The study site is located within the Willamette River watershed (Oregon, USA), which includes free-flowing river segments and a reservoir downstream of the mine. The concentrations of THg in the reservoir fish were 4-fold higher than those further downstream (>90km) from the mine site in free-flowing sections of the river. Mercury stable isotope fractionation analysis showed that the mine tailings (δ202Hg: -0.36 ±0.03‰) had a distinctive isotopic composition compared to background soils (δ202Hg: -2.30 ±0.25‰). Similar differences in isotopic composition were observed between stream water that flowed through the tailings (particulate bound δ202Hg: -0.58‰; dissolved: -0.91‰) versus a background stream (particle-bound δ202Hg: - 2.36‰; dissolved: -2.09‰). Within the reservoir sediment, the Hg isotopic composition indicated that the proportion of the Hg related to mine-release increased with THg concentrations. However, in the fish samples the opposite trend was observed—the degree of mine-related Hg in the fish was lower in the fish with the higher THg concentrations. While sediment concentrations clearly show the influence of the mine, the relationship in fish is more complicated due to differences in methylmercury (MeHg) formation and the foraging behavior of different fish species. The fish tissue 13C and Δ199Hg values indicate that there is higher influence of mine-sourced Hg in fish feeding in a more sediment-based food web and less so in planktonic and littoral-based food webs. Identifying the relative proportion of Hg from local contaminated site source can help inform remediation decisions, especially when the relationship between total Hg concentrations and sources do not show similar covariation between abiotic and biotic media.